Terpenoids as Potential Geroprotectors - Ekaterina Proshkina; Sergey Plyusnin; Tatyana Babak; Ekaterina Lashmanova; Faniya Maganova; Liubov Koval; Elena Platonova; Mikhail Shaposhnikov; Alexey Moskalev (MDPI AG, 2020)
Terpenes and terpenoids are the largest groups of plant secondary metabolites. However, unlike polyphenols, they are rarely associated with geroprotective properties. Here we evaluated the conformity of the biological effects of terpenoids with the criteria of geroprotectors, including primary criteria (lifespan-extending effects in model organisms, improvement of aging biomarkers, low toxicity, minimal adverse effects, improvement of the quality of life) and secondary criteria (evolutionarily conserved mechanisms of action, reproducibility of the effects on different models, prevention of age-associated diseases, increasing of stress-resistance). The number of substances that demonstrate the greatest compliance with both primary and secondary criteria of geroprotectors were found among different classes of terpenoids. Thus, terpenoids are an underestimated source of potential geroprotectors that can effectively influence the mechanisms of aging and age-related diseases.